Correlation of inmates’ rights restrictions aims - Човган, В. О. (Problems of legality, 2014)
The article for the first time poses and examines the problem of purposes of placed on the prisoners’ rights restrictions in light of the requirements of the Constitution of Ukraine, the European Convention on Human Rights and Fundamental Freedoms, Criminal Code and Penitentiary Code of Ukraine. It identifies the common ground of these requirements and some theoretically possible solutions to the problem of its coordination. This article also describes the ambiguity and problematic development of a single scientific approach to understanding the goals and requirements of the inmates’ rights restrictions. Citing some examples, the author demonstrates the relationship between the theoretical and practical nature of the problem. By showing their importance to the national penitentiary activities as the process of rights restrictions’ application to prisoners attention to the importance of international standards on inmates’ rights restrictions is paid.